Inhibition of the chemiluminescence and chemotactic activity of phagocytes for selected Ficus species extract and their lipoxygenase and xanthine oxidase enzyme inhibitory - Shukranul Mawa,; Ibrahim Jantan,; Fadzureena Jamaluddin,; Khairana Husain, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The effects of crude methanol from seven Ficus species on reactive oxygen species (ROS) production were evaluated using luminol based chemiluminescence assay and their inhibition of PMNs chemotaxis was investigated using Boyden chamber technique. Crude methanol of F. aurantiaca, F. parietalis, and F. annulata showed strong activity against PMN chemotaxis with IC 50 values of 1.4, 0.3 and 2.2 µg/mL, respectively, while crude methanol from F. aurantiaca and F. parietalis on whole blood and ROS production of PMNs exhibited high inhibitory activity for luminol enhanced chemiluminescence with IC 50 values of 1.4, 0.9, and 1.0, 0.4 µg/mL, respectively. In xanthine oxidase inhibition assay, crude methanol from F. aurantiaca (stem), F. parietalis (stem), and F. annulata (leaf) exhibited greater than 92% inhibition at concentration of 100 µg/mL (with IC50 values of 0.9, 1.0 and 8.9 µg/mL, respectively) while some extracts of other species showed more than 60% inhibitions at this concentration. In soybean lipoxygenase (SBL) assay, the methanolic extracts of these 3 species showed potent SBL inhibition with IC50 values of 0.3, 0.7, and 6.3 µg/mL, respectively. The overall results suggest that F. parietalis, F. annulata, and F. aurantiaca might be a prospective source of anti-inflammatory mediators and as a source of new immunomodulatory agents.